China’s Confucius Institutes-More Academic and Integrative - Qiang, Zha (International Higher Education, 2013)
The Confucius Institute Headquarters or Hanban recently announced three new major programs that aim to transform Confucius Institutes into an academic unit and an integrative part in their host universities. This article argues that the transformation of Confucius Institutes requires not only resource support but also-and more importantly-a thrifty handle of the difference in university culture in order to form a shared "intersubjective meaning" and a partnership of a "unity with diversity."